1998
DOI: 10.1007/pl00009964
|View full text |Cite
|
Sign up to set email alerts
|

Corticosterone treatment inhibits cell proliferation in the gastric epithelium of suckling rats

Abstract: During the 3rd postnatal week, the rat gastrointestinal tract undergoes major changes which depend on the different factors such as dietary transition and hormones. Glucocorticoids are closely involved in these processes, yet a clear proliferative response to these agents in the gastric epithelium has not yet been established. The aim of this study was to determine the effect of corticosterone on cell proliferation in the gastric mucosa of suckling rats. We also measured plasma corticosterone concentration in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 28 publications
2
26
0
1
Order By: Relevance
“…Previous observations also documented analogous changes in the stomach and colon [1, 2, 4, 5, 6, 7, 9, 10, 12, 14, 15, 28, 29]. It should be noted that a decrease in the values of all parameters is observed.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Previous observations also documented analogous changes in the stomach and colon [1, 2, 4, 5, 6, 7, 9, 10, 12, 14, 15, 28, 29]. It should be noted that a decrease in the values of all parameters is observed.…”
Section: Discussionmentioning
confidence: 71%
“…In well-oriented sections, the number of mitotic or labelled cells and the total number of cells were counted in the whole thickness of the mucosa in randomly selected fields [5, 7]. The slides were carefully moved so that the entire thickness of the gland was analyzed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These maturation changes have been correlated with enhanced glucocorticoid levels (26) and increased epithelial cell migration rate (26). We have shown that plasma corticosteroid levels are highly elevated in food-deprived rats aged 18 and 22 days (27). However, administration of corticosterone inhibited epithelial proliferation of the stomach of fed suckling rats (27) but no effect could be demonstrated in the small intestine (28).…”
Section: Discussionmentioning
confidence: 93%
“…We have shown that plasma corticosteroid levels are highly elevated in food-deprived rats aged 18 and 22 days (27). However, administration of corticosterone inhibited epithelial proliferation of the stomach of fed suckling rats (27) but no effect could be demonstrated in the small intestine (28). Higher levels of corticosterone were also obtained for suckling milkdeprived rats receiving prostaglandin E 2 (PDGE 2 ) (29).…”
Section: Discussionmentioning
confidence: 99%